Assessments of Antibacterial Effects of Aqueous-Ethanolic Extracts of Sida rhombifolia’s Aerial Part - Demeke Debalke; Mastewal Birhan; Amebaye Kinubeh; Muluken Yayeh (The Scientific World Journal)
Infectious diseases are the critical problems of the world as a result of the emergence of different antimicrobial resistant microorganisms due to several reasons like misuses and repeating uses of antibiotics. Because of this, searching of new treatment method is important from natural substances to against those infectious diseases in both human and animals’ aspects. Among those plants, Sida rhombifolia has various roles against those infectious diseases through its different phytochemical components. The objectives of this study were assessing the antibacterial activity of the aqueous-methanol extract of the plant’s aerial part and knowing the phytochemical constituents of the plant. Preliminary phytochemical screening revealed that the extract of S. rhombifolia’s aerial part possesses flavonoids, alkaloids, polyphenols, and quinines. In addition to this, the antibacterial activity of the plant extract was evaluated on five pathogenic bacteria species using agar well diffusion method at different concentrations of plant extracts. Minimum inhibition concentration and minimum bactericidal concentration determinations were done by tetrazolium chloride microtiter dilution assay. The inhibition zone of mean diameters ranging from 0.00 to 7.67mm against all test bacteria was significantly (p<0.05) much less than that of the positive control Chloroamphinicole (30μg/disc) with the range of 14.33mm-15mm of inhibition zone of diameters. The inhibition zones of the tested bacteria at the concentration of 62.5mg/ml were much less than the higher concentration (500mg/ml) and significantly different (p<0.05), whereas the MIC value ranges from 4.62 to 97.22mg/ml and the MBC value ranges from 4.62 to 125.00mg/ml. Even if the plant extract showed antibacterial activity, it was lower than that of other solvent extraction methods; so other solvent extraction methods and fractionates must be conducted to investigate the antibacterial activities of the plant extract on different bacterial strains and species that cause different diseases.